Elasticity Measurement Of Local Taxes And Charges In Forecast Of Own-Source Revenue (PAD) Of Provincial Government In Indonesia - Noch, Muhammad Yamin; Pattiasina, Victor; Purwanto, Hafidz Arif (E-Jurnal Akuntansi; Vol 22 No 1 (2018), 2018)
This research aims to measure the elasticity of local taxes and charges in the framework of Own-Source Revenue (PAD) forecasting of Provincial Government in Indonesia. By using Fully Modified Least Square (FMOLS) method, the result shows that long-term elasticity or local taxes growth of 0.865 is still under GRDP growth, in accordance with the growth of charges of 0.756 shows the same result. While short-term elasticity or local taxes stability of 0.568 gives an overview of local taxes that is not sensitive to changes in GRDP, while the stability of charges of 2.704 shows the result is sensitive to changes in GRDP, however the value of stability is not supported sufficient significance so that the sensitivity factor of PAD is influenced by factor in beyond that. Forecasting result using the model in 2013, both local taxes and charges show better result than actual forecasting shown with smaller Revenue Forecast Error (RFE) value. Keywords:  local taxes, local charges, FMOLS, RFE